Comparative analysis of spatial genetic structure in an ant–plant symbiosis reveals a tension zone and highlights speciation processes in tropical Africa - Rumsaïs Blatrix; Jean Peccoud; Céline Born; Finn Piatscheck; Laure Benoit; Mathieu Sauve; Champlain Djiéto‐Lordon; Christiane Atteke; Jan J. Wieringa; David J. Harris; Doyle McKey (Journal of Biogeography, 2017)
Aim Pleistocene climatic oscillations induced range fluctuations in African rain forest organisms and may have shaped species diversification through allopatric speciation events. We compared the spatial genetic structure of two forest species that live in obligate symbiosis and thus must have experienced the same range fluctuations, as a means to discriminate incipient speciation from transient differentiation simply resulting from past divergence. Location Western central Africa. Methods We genotyped 765 individuals of the tree Barteria fistulosa and 605 colonies of its symbiotic ant Tetraponera aethiops at 12 and 13 microsatellite loci, respectively. We compared the spatial genetic structure of the two symbionts by using Bayesian clustering algorithms, isolation‐by‐distance analyses and clines of synthetic alleles. We used species niche modelling (climatic and soil variables) to investigate ecological variables associated with genetic discontinuities in tree populations. Results The trees and the ants showed congruent patterns of spatial genetic structure. However, the trees showed a very steep genetic discontinuity between groups north and south of latitude 1° N, which was much weaker in the ants. There was no evidence for effective gene flow between the two tree lineages in contact at the transition zone, despite the presence of a few hybrids. Niche modelling did not predict the occurrence of northern trees south of this genetic transition, and vice versa. Main conclusions The genetic discontinuity near latitude 1° N is inferred to be a tension zone resulting from reproductive incompatibilities between previously allopatric tree lineages. This tension zone may have stabilized at a climatic transition (between boreal and austral seasonal regimes), and matches patterns of genetic structure previously observed in other forest plant species. Our results illustrate independent speciation between two species that live in specific and obligate symbiosis and suggest that a tension zone may separate lineages of several central African forest plants near the thermal equator.

Whose truffle is this? Distribution patterns of ectomycorrhizal fungal diversity in T uber melanosporum brûlés developed in multi‐host M editerranean plant communities - Elisa Taschen; Mathieu Sauve; Adrien Taudiere; Javier Parlade; Marc‐André Selosse; Franck Richard (Environmental Microbiology, 2015)
Summary In the M editerranean region, patches of vegetation recovering from disturbance and transiently dominated by shrubs produce one of the world's most prized fungi, the black truffle ( T uber melanosporum ). In these successional plant communities, we have fragmentary knowledge of the distribution of T . melanosporum in space among ectomycorrhizal ( ECM ) host species and in time. Molecular identification of hosts (Restriction Fragment Length Polymorphism) and fungi (Internal Transcribed Spacer sequencing) and quantification of T . melanosporum mycelium (quantitative Polymerase Chain Reaction) were employed to evaluate the presence of T . melanosporum on four dominant ECM host species ( Q uercus ilex , Q uercus coccifera , A rbutus unedo , C istus albidus ) and the extent to which their respective ECM communities shared fungal diversity, over the course of development of truffle grounds, from recent unproductive brûlés to senescent ones where production has stopped. We found that truffle grounds host rich communities in which multi‐host fungal species dominate in frequency. When considering both ECM tips and soil mycelia, we documented a dynamic and spatially heterogeneous pattern of T . melanosporum distribution in soils and a presence of ECM tips restricted to Q . ilex roots. This study advances our knowledge of the ecology of T . melanosporum , and provides insight into the extent of ECM fungal sharing among plant species that dominate M editerranean landscapes.